SMEs' PERCEPTION ON SUPPLY CHAIN RISK: DOES SIZE MATTER? - Hamidatun Khusna Bt Mustafa; Sabariah Yaakub (International Journal of Accounting, Finance and Business, 2020)
Small and Medium Enterprises (SMEs), although a vital component in fostering economic growth of a country, failed to rise to its full potential due to various risks. Using a unique firm size survey data for manufacturing SMEs, we investigate whether firm’s size contribute to the level of perception of three supply chain risks: innovation and technology adoption, access to financing and human capital development. Data was collected in Peninsular Malaysia, yielding a response of 152 companies. Results indicate firm’s size affect how companies perceive level of two supply chain risk (innovation and technology adoption and access to financing) while there were no significant relationship between firm’s size and human capital development risk. Moreover, the result shows these supply chain risks impact depends very much on firm’s size, where the smallest firm are most adversely affected. This study would help Malaysian government focus more on the micro and small firm in dealing with business volatilities.